FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Linda Santioso; Andreas Bambang Daryatno; Albertus Martin (Universitas Kristen Krida Wacana, 2019)
Income smoothing is a way that management use to reduce fluctuations in the reported earnings in accordance with the desired targets through accounting method or transaction. The purpose of the research is to analyze the correlation between firm size, profitability, financial leverage, institutional ownership, CEO duality and board size to income smoothing on manufacturing firms in Indonesia Stock Exchange in the study period of 2015 through 2017, amounted to 156 companies. Samples were selected using purposive sampling method amounted to 57 companies. Data collection techniques used in this research is secondary data that is processed using program SPSS for windows 23.00. The analysis used in this study is the analysis of logistic regression. The result of this research show that profitability variable is significant to income smoothing, while firm size, financial leverage, institutional ownership, CEO duality, and board size are not significant.Keywords: firm size, profitability, financial leverage, corporate governance, and income smoothing